ОПЫТ РАБОТЫ МАЛОЙ АКАДЕМИИИ НАУК ПРИ ИНБЮМ НАН УКРАИНЫ: УСПЕХИ И ПРОБЛЕМЫ - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 2001)
Проанализирован опыт работы биологической секции Малой Академии наук при ИнБЮМ НАН Украины. Сделана попытка систематизации форм работы с одаренной молодежью в области естественных наук.
The work experience of the Small Academy of Sciences at IBSS: issues and achievements
The research experience of the Biological Section of the Small Academy of Sciences at the Institute of Biology of the southern Seas has been analyzed. The educational methods of work with gifted youth in field of natural sciences were systematized.